Hadith Study About Islam, Education and Entrepreneurship - Kamilul Himam; Ahmad Mohammad Tidjani (al-Bunyan: Interdisciplinary Journal of Qur'an and Hadith Studies, 2025)
Hadith, which is also often referred to as sunnah, in addition to discussing the rules, instructions related to the afterlife, also includes discussions about worldly matters, for example hadiths about entrepreneurship. The Prophet explained that the best work is that which is done with one's own hands, namely entrepreneurship. Seeing the reality that is happening at this time, entrepreneurs in Indonesia are still very few, even though the majority of people in Indonesia are mostly Muslim, meaning that there are still few who understand that entrepreneurship is the best job. The Prophet Muhammad SAW greatly praised his people who were willing to work with their skills. This study aims to find out the hadiths about the relationship between Islam and entrepreneurship and how to understand the hadith, to find out what the implications of entrepreneurship are today. The method used in collecting data uses the library research method or literature study, by presenting hadiths about entrepreneurship education, then the data is processed and analyzed using descriptive methods. This study resulted in several conclusions, that the Prophet in his hadith explained that working is a necessity and obligation and entrepreneurship is a choice, in entrepreneurship an entrepreneur must have several characters that must be possessed, namely respecting time, istiqomah, hardworking and responsible. The Prophet also explained in his hadith, that every entrepreneur in running his business, must have good ethics, such as, honest, trustworthy, tolerant, and professional. In entrepreneurship must also be intended and have good goals, namely for the sake of worship in order to achieve Allah's pleasure, to fulfill the needs of life and to fulfill social interests.